Microstructuring tools for sheet bulk metal forming - a designated application for picosecond laser - Häfner, Tom; Reg, Yvonne; Hetzner, Harald; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
In addition to coatings, microstructures can increase abrasion-resisting quality of sheet bulk metal forming tools by influencing friction conditions. The use of ultrashort pulsed lasers offers a possibil-ity for manufacturing flexible microstructures with very high precision. Thus the processing with picosecond laser allows the generation of structures with dimensions down to the range of single microns. Because of the characteristic ablation process temperature sensitive materials can be struc-tured without any heat transfer into the material. Applying appropriate processing parameters avoids complex post-finishing processes because of the achieved good structure qualities without any melt and any material throw-up. For implemention of a fast structuring process with high ablation rates it is shown, that only fluences near the ablation threshold allow a processing result of high quality and with the maximum ablation efficiency.
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KLMEFK.micros
Keywords: Ablation efficiency; Ablation quality; Microstructuring; Picosecond laser; Ultrashort pulsed laser.